Adapting and Validating the Covid-19 Anxiety Scale (CAS-7) in Indonesia - Thiefanee, Gilda; Kumalasari, Asteria Devy (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2024)
There has been a lack of anxiety assessments designed explicitly in the context of COVID-19, particularly screening tools that are easy to understand for diverse demographics and easily administered to accommodate Indonesia’s large population. CAS-7 has proven to be an effectively administrable, reliable, and valid assessment to measure pandemic‑related anxiety among the Indian population. This study aimed to adapt and validate CAS-7 to provide a reliable and valid screening tool to timely identify citizens of Indonesia suffering from pandemic-related anxiety and assign them suitable interventions. There were 1,121 subjects from 29 provinces participated in the study. Factorial validity was tested with Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) in JASP 15.0.0. while convergent validity, test-retest reliability, and internal reliability were tested with Pearson product-moment correlation coefficient, intraclass correlation coefficient, and Cronbach’s alpha in SPSS 25. The adaptation of CAS-7 has proven to be a satisfactory, reliable, and valid screening tool for identifying citizens of Indonesia suffering from pandemic-related anxiety, with changes made in item arrangement and factor interpretation.